The Use of Word Wall Media to Improve Students’ Vocabulary Mastery - Nurhayati; Togatorop, Ckristina Wati (Proceeding International Conference on Education, 2024)
This study aimed to determine whether word wall media can enhance vocabulary mastery among seventh-grade students in class 7D at SMP ADVENT UNKLAB AIRMADIDI during the second semester of the 2023/2024 academic year. The research was conducted over two cycles using Classroom Action Research of the Kemmis and McTaggart design, which includes four phases: planning, acting, observing, and reflecting. The participants comprised 34 students (26 males and 8 females). Data were collected through pre-tests and post-tests to assess vocabulary mastery. The pre-test results showed that only 29% of students (10 students) met the minimum mastery criteria (MMC) score of 70. After implementing word wall media in Cycle 1, the post-test revealed a significant improvement, with 47% (16 students) achieving mastery. However, this still did not meet the success indicator of 80%. In Cycle 2, following further treatment, the post-test results improved dramatically to 88%, with 30 students achieving mastery. This indicates that the use of word wall media significantly enhances students' vocabulary mastery. The study recommends that English teachers incorporate word wall media into their instructional strategies to improve vocabulary outcomes.